2015
DOI: 10.1177/0394632015586134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aspartame and saccharin on the rat liver: Biochemical, molecular, and histological approach

Abstract: The current work was undertaken to settle the debate about the toxicity of artificial sweeteners (AS), particularly aspartame and saccharin. Twenty-five, 7-week-old male Wistar albino rats with an average body weight of 101 ± 4.8 g were divided into a control group and four experimental groups (n = 5 rats). The first and second experimental groups received daily doses equivalent to the acceptable daily intake (ADI) of aspartame (250 mg/Kg BW) and four-fold ADI of aspartame (1000 mg/Kg BW). The third and fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 34 publications
4
25
1
4
Order By: Relevance
“…Until the present study, there was no evidence that guarana SD could contribute to liver or gastric damage. In parallel, only a few studies have demonstrated a potential risk of hepatotoxicity under chronic exposure to aspartame [76, 77] or acesulfame K [12]. Thus, our data clarify this question by demonstrating that the excessive consumption of carbohydrates (but not guarana per se) is the main contributor to steatosis and oxidative stress in the liver.…”
Section: Discussionsupporting
confidence: 61%
“…Until the present study, there was no evidence that guarana SD could contribute to liver or gastric damage. In parallel, only a few studies have demonstrated a potential risk of hepatotoxicity under chronic exposure to aspartame [76, 77] or acesulfame K [12]. Thus, our data clarify this question by demonstrating that the excessive consumption of carbohydrates (but not guarana per se) is the main contributor to steatosis and oxidative stress in the liver.…”
Section: Discussionsupporting
confidence: 61%
“…Amin et al reported that Sac decreased body weight, fasting blood glucose, total and LDL-cholesterol, and Tg levels in Rattus Norvegicus albino rats, but increased liver transaminases (TANs) compared to a control group fed normal chow [ 19 ]. Alkafafy et al compared the consumption of Sac versus a normal diet without Sac in Wistar albino rats and found that Sac decreased body weight and increased TANs levels [ 20 ]. Several other studies noted body weight reduction and several changes in biochemical liver function tests [ 21 , 22 ]; however, none of these studies compared Sac to fructose.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is highly correlated with ASP toxicity [ 13 , 14 ]. ASP induces reactive oxygen species formation and cytotoxicity, due to an imbalance in the antioxidants/oxidative system in hepatocytes [ 15 ]. It has been shown that free radicals may cause membrane destruction through the oxidative corruption of lipids, proteins, and DNA [ 16 ].…”
Section: Introductionmentioning
confidence: 99%